Identification of QTLs/ Candidate Genes for Seed Mineral Contents in Common Bean (Phaseolus vulgaris L.) Through Genotyping-by-Sequencing - Nazir, Muslima; Mahajan, Reetika; Mansoor, Sheikh; Rasool, Sheezan; Mir, Rakeeb Ahmad; Singh, Ravinder; Thakral, Vandana; Kumar, Virender; Sofi, Parvaze A.; El-Serehy, Hamed A.; Hefft, Daniel Ingo; Zargar, Sajad Majeed (Frontiers in Genetics, 2022)
We have been witnessing through ages that common bean is consumed as important food staple crop on global scale by humans to derive nutrition. Since its domestication wide spectrum, phenotypic and genotypic investigations are carried out for unravelling the potential of this crop to understand the process of nutrient accumulation and other desirable characteristics. Common bean is one of the essential legumes crops due to its high protein and micronutrient content. The balance in the micronutrients is critical for growth and development of plants as well as humans. Iron (Fe), Zinc (Zn), Copper (Cu), Manganese (Mn), Magnesium (Mg), Calcium (Ca) and Molybdenum (Mo) are some of the important micronutrients present in legumes. Thus, we aimed to investigate the quantitative trait loci’s (QTLs)/ single nucleotide polymorphisms (SNPs) to identify the candidate genes associated with the micronutrients by genotype by sequencing (GBS). In our investigation, through GBS we identified SNPs linked with traits and assessed seven micronutrients in 96 selected common bean genotypes for screening nutrionally rich genotypes. Among 96399 SNPs total identified through GBS, 113 SNPs showed significant phenotypic variance, ranging from 13.50 to 21.74%. SNPs associated to most of the seed micronutrients (Mg, Mn, Fe, Ca, Cu) were found on chr3 & chr11 (Mg, Mn, Mo, Ca, Zn). The findings from this study could be used for haplotype-based selection of nutritionally rich genotypes and for marker assisted genetic enhancement of common bean. Further, the identified SNPs for candidate genes/transporters associated with micronutrient content may pave way for enrichment of seeds by employing genomics-assisted breeding programmes.